1974
DOI: 10.1128/aac.5.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Therapeutic and Pharmacological Evaluation of Amoxicillin and Ampicillin Plus Probenecid for the Treatment of Gonorrhea

Abstract: Single doses of 3.5 g of ampicillin with 1.0 g of probenecid or of 3.0 g of amoxicillin alone were administered orally to 58 males and 56 females with uncomplicated gonococcal infection. The failure rate for genital or anal infection, or both, was 1.7% for ampicillin plus probenecid and 4.2% for amoxicillin alone. However, patients with oropharyngeal infection responded poorly. Seventy-five isolates of Neisseria gonorrhoeae recovered from patients in this study were all inhibited by 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The results of these pharmacokinetic studies in infants and children are consistent with those reported in adult volunteers (2,3,8). Cyclacillin was rapidly absorbed from the gastrointestinal tract after ingestion of the suspension in fasting and nonfasting subjects, and its bioavailability was unaffected by the feeding status in this age group.…”
supporting
confidence: 81%
“…The results of these pharmacokinetic studies in infants and children are consistent with those reported in adult volunteers (2,3,8). Cyclacillin was rapidly absorbed from the gastrointestinal tract after ingestion of the suspension in fasting and nonfasting subjects, and its bioavailability was unaffected by the feeding status in this age group.…”
supporting
confidence: 81%
“…Karney et al (1974) reported 43 % of strains as relatively resistant (MIC .0-16 ptg/ml); we found a figure of 47 5 %.…”
Section: Discussionsupporting
confidence: 39%
“…We found that the proportion of strains relatively resistant to amoxycillin was 46%. In an evaluation of amoxycillin in the treatment of gonorrhoea in the USA, Karney et al (1974) reported a figure of 39%.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of these studies reported adverse reactions in 569 patients and the safety of 11 drugs was assessed [27][28][29][30][31][32][33][34][36][37][38][39][40][41][44][45][46]49,50]. Similarly, 19 studies focused on oral monotherapy [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. These studies of oral drugs involved 3782 patients, and compared the efficacy of 11 antibiotics.…”
Section: Literature Search Process and Study Characteristicsmentioning
confidence: 99%